Innovation in Payments : Opportunities and Challenges for EMDEs - World Bank; International Monetary Fund (World Bank, Washington, DC, 2022)
The global economy is undergoing a rapid digital transformation that is changing many conventional notions about our behavior and preferences. This includes the way in which we, as consumers, as businesses, or in interactions with government, seek out goods and services and pay for them or how we receive money from others or transfer it to family or friends. As the payments industry undergoes radical changes due to digital transformation, users, providers of payment services, and regulators are adapting to the new dynamics at varying paces. This note discusses the most significant innovations in payments and their key impacts and implications on users, banks and other payment service providers, regulators, and the overall structure of the payments market. The note places special emphasis on how emerging markets and developing economies (EMDEs) can reap the benefits of payment innovations in terms of costs, convenience, accessibility, and inclusion for individuals and firms, and allow them to leapfrog development of their payments markets and effectively support economic activity.